Microshear Bond Strength of OptiBond All-In-One Self-adhesive Agent to Er:YAG Laser Treated Enamel After Thermocycling and Water Storage - Kasraei, Shahin; Yarmohammadi, Ebrahim; Ghazizadeh, Mohammad Vahid (Journal of Lasers in Medical Sciences, 2016)
Introduction: This study aimed to compare the microshear bond strength of composite to enamel treated with Erbium-Doped Yttrium Aluminum Garnet (Er:YAG) laser using a self-etch one step bonding agent. Methods: Seventy-six enamel surfaces were prepared from 38 sound human third molar teeth. Specimens were randomly divided into four groups of 18. The enamel surface in half the specimens was irradiated with Er:YAG laser. One extra specimen from each group was evaluated under a scanning electron microscope (SEM). Composite micro-cylinders were bonded to the specimen surfaces using OptiBond All-In-One (OB) adhesive agent and stored in distilled water for 24 hours. Half the specimens were thermocycled (2000 cycles) and stored in distilled water at 37°C for three months (TW). The microshear bond strength of composite to enamel was measured using a universal testing machine at a crosshead speed of 1 mm/min. The fractured surfaces were evaluated under a stereomicroscope at ×40 magnification to determine the mode of failure. Data were analyzed using repeated measures analysis of variance (ANOVA) and t test. Results: The mean values (±standard deviation) were 17.96 ± 2.92 MPa in OB group, 22.29 ± 4.25 MPa in laser + OB group, 18.11 ± 3.52 MPa in laser + OB + TW group and 9.42 ± 2.47 MPa in OB + TW group. Repeated measures ANOVA showed that laser irradiation increased the microshear bond strength (P < 0.001). Bond strength decreased when the samples were thermocycled and stored for three months (P < 0.001). The interaction effect of water storage and laser treatment on bond strength was significant (P < 0.05). Conclusion: Enamel surface preparation with Er:YAG laser is recommended to enhance the durability of the bond of self-etch bonding systems to enamel.